Health risks associated with genetic alterations in internal clock system by external factors - Khan, Suliman (Int J Biol Sci, 2018)
The circadian system maintains the main aspects of physiological and behavioral processes. Both circadian rhythm and sleep impact an organism's health through interaction with environmental factors. Variations in external factors influence the functionality of clock genes and disrupt 24-hour rhythmic cycle. The disrupted circadian rhythm and disregulated sleep affect an organism's health, thereby causing several disorders including cancer, depression and cardiac disorders. Considering the role of clock genes and environmental factors, extensive investigation is required focusing on pathways involved in development of life-threatening disorders. This review identifies the major risks and associated factors related with disruption in circadian system and sleep.